PanGen-Fam: Spanish registry of hereditary pancreatic cancer. Issue 14 (September 2015) - Mocci, E.; Guillen-Ponce, C.; Earl, J.; Marquez, M.; Solera, J.; Salazar-López, M.-T.; Calcedo-Arnáiz, C.; Vázquez-Sequeiros, E.; Montans, J.; Muñoz-Beltrán, M.; Vicente-Bártulos, A.; González-Gordaliza, C.; et al.
Abstract Purpose To describe the organisation of the registry and the preliminary results in terms of characteristics of high-risk pancreatic ductal adenocarcinoma (PDAC) families recruited to date and findings of the screening programme. To compare early onset sporadic cases (⩽50 years), sporadic cases (>50 years) and cases with family history of cancer, for PDAC possible risk factors. Methods/patients Families with hereditary cancer syndromes predisposing to PDAC were recruited from two main sources: Spanish hospitals participating in PanGenEU, a pan-European multicentre case–control study, and their genetic counseling unit. Individuals at high-risk of PDAC were enrolled into a screening programme, consisting of Endoscopic ultrasound, computerised tomography, magnetic resonance imaging. Genetic testing of candidate genes was offered according to each patient's risk. Results Among 577 consecutive PDAC cases, recruited via PanGenEU, 36 (6%) had ⩾2 first-degree relative with PDAC: Familial pancreatic cancer (FPC). So far PanGen-Fam has recruited 42 high-risk PDAC families; 25 (60%) had FPC. Five index cases with cancer were positive for BRCA2 and one for BRCA1 germline mutations. In the second year of prospective PDAC screening, one neuroendocrine tumour and a high-grade dysplasia lesion suspicious of carcinoma were diagnosed among 41 high-risk individuals. Furthermore EUS detected chronic-pancreatitis-like parenchymal changes in 15 patients. Concluding statement The identification and recruitment of PDAC high-risk families into the PanGen-Fam registry provides an opportunity to detect early onset cancer and precursor pancreatic cancer lesions at a potentially curative stage and to increase the knowledge of the natural history of the disease.